(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article investigates the narratives surrounding the online public debate of gamer communities on Twitter during the political rallies for the bicentennial of Brazilian Independence Day, occurring in September 2022. The analysis is based on two collections conducted between August 31 and September 14, resulting in one corpus of 11,607 interactions made by 4,090 accounts, and another of 59 interactions by 47 accounts. The results reinforce the perception that the event was not a relevant topic in the observed gamer communities, pointing to a possible loss of support by former president Jair Bolsonaro among gamers.